P. falciparum Enhances HIV Replication in an Experimental Malaria Challenge System - Orlov, Marika; Vaida, Florin; Finney, Olivia C.; Smith, David M.; Talley, Angela K.; Wang, Ruobing; Kappe, Stefan H.; Deng, Qianqian; Schooley, Robert T.; Duffy, Patrick E. (PLOS ONE, 2012)
Co-infection with HIV and P. falciparum worsens the prognosis of both infections; however, the mechanisms driving this adverse interaction are not fully delineated. To evaluate this, we studied HIV-1 and P. falciparum interactions in vitro using peripheral blood mononuclear cells (PBMCs) from human malaria naïve volunteers experimentally infected with P. falciparum in a malaria challenge trial.PBMCs collected before the malaria challenge and at several time points post-infection were infected with HIV-1 and co-cultured with either P. falciparum infected (iRBCs) or uninfected (uRBCs) red blood cells. HIV p24Ag and TNF-α, IFN-γ, IL-4, IL-6, IL-10, IL-17, and MIP-1α were quantified in the co-culture supernatants. In general, iRBCs stimulated more HIV p24Ag production by PBMCs than did uRBCs. HIV p24Ag production by PBMCs in the presence of iRBCs (but not uRBCs) further increased during convalescence (days 35, 56, and 90 post-challenge). In parallel, iRBCs induced higher secretion of pro-inflammatory cytokines (TNF-α, IFN-γ, and MIP-1α) than uRBCs, and production increased further during convalescence. Because the increase in p24Ag production occurred after parasitemia and generalized immune activation had resolved, our results suggest that enhanced HIV production is related to the development of anti-malaria immunity and may be mediated by pro-inflammatory cytokines.